1990
DOI: 10.1148/radiology.174.2.2296659
|View full text |Cite
|
Sign up to set email alerts
|

Bone scans with one or two new abnormalities in cancer patients with no known metastases: reliability of interpretation of initial correlative radiographs.

Abstract: To determine the reliability of radiographs obtained for correlation with bone scans showing one or two new abnormalities in cancer patients without known metastases, a retrospective study of 306 scans showing such lesions was performed. Overall, 14% of the lesions proved to be malignant. The initial radiographic interpretation was normal for 43% of the new bone scan lesions; 17% of these lesions were metastases. A benign process was identified on radiographs for 38% of the abnormalities; only one (1%) was a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 0 publications
0
10
0
3
Order By: Relevance
“…2 Our study demonstrated that a fair proportion of our patient staging using the current BS/TXR work-up was not true according to the gold standard. Conventional wisdom is often seen as an obstacle to introducing new theories-a cause of inertia.…”
Section: Authors' Disclosures Of Potential Conflicts Of Interestmentioning
confidence: 66%
“…2 Our study demonstrated that a fair proportion of our patient staging using the current BS/TXR work-up was not true according to the gold standard. Conventional wisdom is often seen as an obstacle to introducing new theories-a cause of inertia.…”
Section: Authors' Disclosures Of Potential Conflicts Of Interestmentioning
confidence: 66%
“…The only strong criteria suggesting metastatic disease to the spine is the presence of multiple new abnormalities; the reported incidence of metastases with only 1 or 2 new bone scan abnormalities ranges from Ͻ10% to 64%. [1][2][3][4] Distinguishing benign from malignant lesions in cancer patients on planar bone scintigraphic images can often be a diagnostic dilemma. This dilemma is often resolved by further correlation of the scan findings with …”
Section: Discussionmentioning
confidence: 99%
“…It is generally agreed that a variation of almost 50% of normal bone tissue mass is necessary for detection [13,17]. Thus, in breast carcinomas, radiographic signs are visible six months later than those seen on scintigraphy [20].…”
Section: Plain Filmsmentioning
confidence: 99%